Enhancing communication skills in diabetes care: an observational study regarding the impact of role-playing training for medical staff - Miyako Kishimoto; Yuri Kaneko; Akiko Wakui-Kimura; Yuko Tachibana; Fumihiko Sato; Takako Kikuchi; Yumi Matsushita; Mika Hashiguchi; Yuka Imai; Erika Sakanaya; Ikuko Senga; Eri Kaido; et al. (BMC Medical Education, 2025)
Abstract Introduction Effective communication is crucial for supporting people with diabetes, yet many medical staff feel unsure about their skills in this area. We evaluated role-playing seminars as a method to improve communication skills among medical staff. Methods From 2008 to 2024, we conducted 78 seminars with 2,458 participants, including nurses, dietitians, and pharmacists. Participants engaged in realistic simulated scenarios based on common clinical situations of patient-medical staff interactions, taking on roles as patients (patient performers), medical staff (medical staff performers), and observers. Due to the COVID-19 pandemic, some seminars were held online. Participants were asked to answer a questionnaire regarding their background, impressions of playing individual roles, general comments regarding the seminar, changes in their patient interactions, the possibility of conducting this seminar at their facilities, and impressions of online seminars compared with those of in-person seminars. Results The responses of the participants to these seminars were mostly positive. The representative responses indicated that patient performers understood better patients’ feelings and medical staff performers had a chance to recognize their insufficient knowledge. The observers also had the chance to learn new communication skills by observing the conversations of other role-players. Compared with in-person seminars, the positive aspects of online seminars were a reduction in time and travel costs and the removal of geographical obstacles. The negative aspects were mostly technology-related concerns. Conclusion Training seminars using in-person or online role-playing provided medical staff with opportunities and support to improve their communication skills. Further research on measures to improve the communication skills of medical staff and ways to evaluate their efficacy is warranted.